Transparent and flexible fingerprint sensor array with multiplexed detection of tactile pressure and skin temperature - Byeong Wan An (Nature Portfolio, 2018)
Next-generation mobile security devices require fingerprint sensors that can be incorporated directly into the display. Here, Park et al. demonstrate a highly transparent, multifunctional capacitive fingerprint sensor array that simultaneously detects tactile pressure and finger skin temperature.